2014
DOI: 10.9734/bjmmr/2014/5444
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Serum Albumin and Neutrophil-Lymphocyte Ratio are Associated with Prolonged Hospital Stay Following Colorectal Cancer Surgery

Abstract: Aims-Colorectal cancer is the third most common cancer in European populations. It has been shown previously that neutrophil-lymphocyte ratio (NLR), pre-operative albumin, and haemoglobin are useful prognostic indicators. The aim of this study was to assess how these factors influence the length of postoperative stay (LOS) following colorectal cancer surgery.Methodology-All patients undergoing elective colorectal resections for malignancy between 2010 and 2011 in Pilgrim Hospital, Boston, U.K. were considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
2
18
0
6
Order By: Relevance
“…Finally, our study showed that preoperative inflammation was associated with a longer postoperative LOS. This is consistent with previous studies, which showed that elevated NLR predicted perioperative complications and was associated with increased LOS for patients undergoing resection for CRC [15,30]. This finding has profound implications for patient care and highlights the usefulness of a simple, inexpensive biomarker that correlates the inflammatory state with colon cancer to its impact on hospitalisation.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, our study showed that preoperative inflammation was associated with a longer postoperative LOS. This is consistent with previous studies, which showed that elevated NLR predicted perioperative complications and was associated with increased LOS for patients undergoing resection for CRC [15,30]. This finding has profound implications for patient care and highlights the usefulness of a simple, inexpensive biomarker that correlates the inflammatory state with colon cancer to its impact on hospitalisation.…”
Section: Discussionsupporting
confidence: 91%
“…4 Sonoda et al, Montomoli et al, and Gohil et al, showed that the preoperative serum albumin has an impact on the morbidity following colorectal surgery in their respective studies. [8][9][10] In the present study preoperative serum albumin less than 3.5g/dl has highest complication (48.9%) and death (14.2%) than albumin more than or equal to 3.5g/dl (3.1% and 0%) which is statistically significant with a p value less than 0.0001 and the majority of complications occurred in patients with albumin less than 2.5g/dl to 3g/dl. This study implies that as the albumin level decreases, the risk of postoperative morbidity and mortality increases.…”
Section: Discussionsupporting
confidence: 48%
“…This finding was supported by Kubo et al [17] who found that infectious complications were significantly associated with the NLR. Similarly, Gohil et al [18] reported that the preoperative NLR value was associated with an increased hospital length of stay.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, Gohil et al . reported that the preoperative NLR value was associated with an increased hospital length of stay.…”
Section: Introductionmentioning
confidence: 99%